Vibrações livres de viga de seção transversal variável - Oliveira, Carlos Frederico da Silveira (2018)
Submitted by maria angelica Varella (angelica@sibi.ufrj.br) on 2018-01-03T13:42:33Z No. of bitstreams: 1 Carlos Frederico da Silveira Oliveira.pdf: 647755 bytes, checksum: c814522c9d1a6f5a819e2cce1088856f (MD5)